2017
DOI: 10.1177/0956462417724586
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and spatial disparity in HIV prevalence among incarcerated population in the US: A state-level analysis

Abstract: The purpose of this study was to explore empirically the presence of any spatial and demographic disparity in the Human Immunodeficiency Virus (HIV) infection rate among the prison inmates across 48 states in the US and compare the results for 2000 and 2010. HIV infection is a severe health issue for incarcerated populations in the US. In 2010, the rate of diagnosed HIV infection among inmates in state and federal prisons was five times more than the nonincarcerated population. The National Prisoner Statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…4 These differences are also seen in other regions, such as eastern Europe and central Asia (4.1% vs. 0.5%, both regions), western Europe (4.6% vs. 0.2%) 5 and North America (1.5% vs. 0.5%). 1 Similar to the results reported by Bose, 1 high subnational level disparities in HIV prevalence among the incarcerated Peruvian population are evident (Figure 1), where Amazonas is the region with the highest prevalence (0.93%), followed by Loreto (0.88%) and Lima (0.74%). In addition, 5 regions are above the incarcerated prevalence (0.47%) and 14 above the general population of Peru (0.3%).…”
Section: Hiv In Prison: Results From a National Prison Census In Perusupporting
confidence: 85%
See 3 more Smart Citations
“…4 These differences are also seen in other regions, such as eastern Europe and central Asia (4.1% vs. 0.5%, both regions), western Europe (4.6% vs. 0.2%) 5 and North America (1.5% vs. 0.5%). 1 Similar to the results reported by Bose, 1 high subnational level disparities in HIV prevalence among the incarcerated Peruvian population are evident (Figure 1), where Amazonas is the region with the highest prevalence (0.93%), followed by Loreto (0.88%) and Lima (0.74%). In addition, 5 regions are above the incarcerated prevalence (0.47%) and 14 above the general population of Peru (0.3%).…”
Section: Hiv In Prison: Results From a National Prison Census In Perusupporting
confidence: 85%
“…The reasons could be related to the social marginalization, violence, stigma and discrimination, risk of sexual victimization and little or no access to HIV prevention that women encounter in prison. 1 The major limitations of this study are the cross-sectional nature of the data and that the presence of HIV infection was assessed using self-reported data. However, in low middle-income countries, these kinds of surveys are frequently done.…”
Section: Hiv In Prison: Results From a National Prison Census In Perumentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, numerous studies have shown that health insurance, which is related to socioeconomic status, plays an important role in the survival of HIV patients. Patients who are insured survive longer than those who lack health insurance, because they are more likely to have access to medical services [ 9 - 11 ]. Understanding the geographic variation of HIV/AIDS mortality and HIV infection could help identify high-burden areas.…”
Section: Introductionmentioning
confidence: 99%